CANCER NANOTECHNOLOGY: NANOPARTICULATE DRUG DELIVERY FOR THE TREATEMENT OF CANCER - Hemant, Ksy; Raizaday, Abhay; Sivadasu, Praveen; Uniyal, Swati; Kumar, S. Hemanth (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
In 21st century scientist all around are trying to formulate the new drug delivery with better efficacy and effectiveness to treat cancer. So their focus has been shifted toward the Nano based drug delivery system because nanotechnology plays with the dimension of the matter typically on the 0.2-to 100-nm scale (Nano scale). When the matter is size reduced its properties changes this is because at the Nano scale the percentage of atoms at the surface of a material becomes more significant. The interesting part of nanotechnology is that when the matter is in bulk possess relatively constant physical properties regardless of their size, but at the Nano scale the matter behave in the different ways. This is because when the material becomes smaller the percentage of atoms at the surface increases relative to the total number of atoms of the material bulk. This can lead to unexpected properties of nanoparticles which are partly due to the surface of the material dominating over the bulk properties. Hence nanotechnology is playing a important role in developing better and effective drug delivery system to fight against cancer. Â